KODIFIKASI AL-QUR`AN DAN HADITS PERSPEKTIF HISTORIS - Mohammad Fattah; Matsna Afwi Nadia (Reflektika, 2019)
This article examines the historical review of the codification of the Qur'an and Hadith from the time of the Apostle saw until it was recorded as a Mushaf in the time of Khulafa al-Rasyidin by looking at the processes of its formation, both during the time of the Prophet and the times after it is essential, to remind Muslims that the Qur'an is a humane manifestation of Kalamullah. The urgency of this discussion is to affirm that historically, the authenticity of the Quran has been assured since its derivation. The review in this article focuses on four issues: First, the Definition of the terms Qur'an and Hadith. Second, the history of the codification of the Qur'an and Hadith. Third, the mapping of the main themes of the Qur'an and Hadith. Fourth, a review of the specialties of the Qur'an